Livelihood Information Endowment as a Correlate of Material Quality of Life among Rural Women in Southwest, Nigeria - ADENIYI RHODA TITILAYO; Taofeeq Oyedeji YEKINNI (Journal of Agricultural Extension, 2023)
This study examined the livelihood information endowment (LIE) as a correlate of Material Quality of life (MQoL) among rural Women in Southwest Nigeria. Multistage sampling procedure was used to select 384 respondents using interview schedule. Data collected on socioeconomic characteristics, LIE (livelihood information sought and sources of information); constraints to LIE and MQoL were analysed with percentages, weighted mean score, mean, standard deviation, Pearson Product Moment Correlation and Chi-square at ?0.05.  Result showed that most of the respondents were cooperative society members (51.6%) with mean year of former education being 8.0±4.62 years. The mostly accessible information source was Radio (1.43); with LIE being high for 55.7%.  However, respondents’ most prominent constraint to LIE was network problem (0.40); which was high for 53.4%.  The respondents’ MQoL status was low for 52.1%, as most did not possess landed properties (58.1%); with the most material possessed compared with peers being kitchen utensils (0.90). Significant relationship existed between respondents’ MQoL and years of experience of non-agricultural activities (r=0.137), LIE (r=0.134), social group belonged (r=0.153), cosmopoliteness (?2=2229.870) and constraint to LIE (r=-0.017). Constraints to LIE inform the respondents’ MQoL status. Therefore, appropriate strategies to combat constraints to the LIE should be embarked on.